DNA-binding properties and secondary structural model of the hepatocyte nuclear factor 3/fork head domain. - Li, C (1993)
An 84-amino acid segment of QRF-1 [glutamine (Q)-rich factor 1], a newly cloned, B-cell-derived DNA-binding protein, shows significant sequence homology with the DNA-binding domains of the hepatocyte nuclear factor 3/fork head family of proteins. Here we demonstrate that this 84-amino acid domain is necessary and sufficient for DNA binding. We also propose a secondary structural model for the domain. At the N-terminal portion of the model, a basic hook structure is followed by two amphipathic helices separated by a turn. Invariant amino acid residues within the two proposed helices form the hydrophobic cores. An aromatic kink and a third amphipathic helix comprise the center of the domain. At the C terminus, two variable-length loops flank a putative 7-amino acid helix followed by a short basic region.